2014
DOI: 10.2119/molmed.2013.00164
|View full text |Cite
|
Sign up to set email alerts
|

The Role of HMGB1 in the Pathogenesis of Inflammatory and Autoimmune Diseases

Abstract: High-mobility group box 1 (HMGB1) protein is a highly abundant protein that can promote the pathogenesis of inflammatory and autoimmune diseases once it is in an extracellular location. This translocation can occur with immune cell activation as well as cell death, with the conditions for release associated with the expression of different isoforms. These isoforms result from posttranslational modifications, with the redox states of three cysteines at positions 23, 45 and 106 critical for activity. Depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
199
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(214 citation statements)
references
References 72 publications
1
199
0
2
Order By: Relevance
“…HMGB1 is a well-known endogenous ligand of TLR4 that has the ability to trigger an inflammatory response [23][24][25]. HMGB1-TLR4 interaction results in downstream activation of NFκB, and subsequent inflammation via generation of PIC and reactive oxygen species [67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMGB1 is a well-known endogenous ligand of TLR4 that has the ability to trigger an inflammatory response [23][24][25]. HMGB1-TLR4 interaction results in downstream activation of NFκB, and subsequent inflammation via generation of PIC and reactive oxygen species [67].…”
Section: Discussionmentioning
confidence: 99%
“…The release of HMGB1 marks the initiation of host defense or inflammatory tissue repair mechanisms [21]. Receptor blocking studies have shown that HMGB1 is a strong endogenous ligand of TLR4 receptor [22][23][24][25]. TLR4 is a receptor found on the cell surface that mediates the proinflammatory effects [26,27] of its ligands through the NFkB signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cells, the nucleus contains approximately 1 HMGB protein for every 10 nucleosomes (90). In addition to roles in DNA-dependent events, HMGB proteins sense cellular stress and function as extracellular cytokines, contributing to inflammatory and immune responses (91).…”
Section: High Mobility Group Proteinsmentioning
confidence: 99%
“…In this study, we detected the nuclear expression of HMGB1 in some of astrocytes, microglia and a few neurons in adult mouse spinal cord, which supplies more information to characterize the expression of HMGB1 in CNS and helps in discovering the potential CNS specific functions of HMGB1. Extracellular HMGB1, which is released passively by death cells or actively by stimulated cells such as macrophages, has been reported to play a key role in autoimmune diseases (Magna and Pisetsky, 2014), allograft rejection (Xia et al, 2014), ischemic stroke (Hayakawa et al, 2012), traumatic brain injury (Laird et al, 2014), and neurodegenerative diseases (Fang et al, 2012) as an inflammatory mediator. MS/EAE is a CNS specific autoimmune disease, which happens in adult human being or is induced in adult animal.…”
Section: Discussionmentioning
confidence: 99%